Effects of Co as an Alloying Element and Heat Treatment Processes on the Properties of High Speed Steels - Toptop, Guven Orkun; Kisasoz, Alptekin; Karaaslan, Ahmet (CARL HANSER VERLAG, 2012)
In this study, effects of Co as an alloying element and different heat treatments processes on the properties of DIN 1.3243 and 1.3343 were investigated. Austenitising and tempering temperatures are critical parameters for steel hardening. Also, Co has critical effect on mechanical properties of high speed steels. Samples were subjected to two different austenitising temperatures with two tempering temperatures. Effects of process parameters on the mechanical properties and tooling abilities of the specimens were investigated. Specimens were characterized by Rockwell hardness tests and tooling abilities of the specimen were determined by characterizing the number of screws that were fabricated with specimens. According to results of experiments, Co has any effect on the hardness of specimens after the austenitising and tempering processes. Moreover, tool life of the specimens were increased by the higher hardening temperatures, the lower tempering temperatures and the presence of Co as an alloying element, because of the positive effect of Co on the hot hardness and hot strength.
Keywords: BEHAVIOR; Materials Science